Analisis Kesehatan Mental (Burnout) Pegawai Badan Kesatuan Bangsa Dan Politik Kab. Karawang - Agustian, Muhamad Alif; Fadli, Uus Muhamad Darul; Rosmawati, Ery (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Burnout is a problem that occurs at the National Unity and Political Agency of the District. Karawang. This research aims to analyze and find out the factors that cause burnout, the impact of burnout, and to find out what strategies can minimize burnout in employees. This research is located at the office of the National Unity and Political Agency, Kab. Karawang. The research informants were secretariat staff, national insight analysis staff, and community staff. Primary data was collected through interviews, observation, documentation, and secondary data obtained from library research. Validity test using data triangulation and content analysis. The results of the research show that fatigue is an influential factor in causing burnout. The impact of burnout on employees is physical fatigue due to urgent tasks and receiving guests outside working hours. The strategy to minimize burnout is to create a conducive working atmosphere, providing balance. between challenge and comfort, creating a good work culture, and creating a good and comfortable environment.